Bioluminescence in an Undescribed Species of Carnivorous Sponge (Cladorhizidae) From the Deep Sea - Martini, Séverine; Schultz, Darrin T.; Lundsten, Lonny; Haddock, Steven H. D. (Frontiers in Marine Science, 2020)
One dominant ecological trait in the dimly-lit deep-sea is the ability of organisms to emit bioluminescence. Despite its many ecological roles in deep-sea ecosystems, the presence of inherent bioluminescence in marine sponges has been debated for more than a century. This work reports repeated observations of luminescence from six individuals of an undescribed carnivorous sponge species (Cladorhizidae) sampled near 4,000 m depth off Monterey Bay (California, USA). These are the first fully documented records of bioluminescence in the phylum Porifera. Videos and photographs of the sponges’ bioluminescence were recorded on board after collection and in vitro bioluminescence assays indicate that the bioluminescence system is a coelenterazine-based luciferase. Coelenterazine luciferin is already described in various organisms such as cnidarians, chaetognaths, copepods, cephalopods, ctenophores, ostracods, and some mysid or decapod shrimps. Based on these observations we discuss new ecological hypotheses of functional traits such as bioluminescence and carnivory in deep sea organisms.